Strategic Renewal and Innovation Model in Zakat, Infaq, and Sadaqah Muhammadiyah (Lazismu) Yogyakarta - Dinar Apriyanto; Wahyu Eko Pujianto; M. Husni Tamrin; Supriyadi (Aplikasi Administrasi: Media Analisa Masalah Administrasi, 2023)
This research aims to analyze how the Strategic renewal and innovation of Lazismu Yogyakarta related to the management and distribution of zakat. This research uses a qualitative approach using a case study strategy. Data collection was done by conducting observations and interviews. Data analysis includes data reduction, data presentation, and conclusion and verification. The results showed that the management and distribution of zakat lazismu Yogyakarta using Strategic renewal which includes: 1) strategic renewal context which includes technological transition through the use of the Lazismudiy.or.id website, and the utilization of social media; 2) Strategic renewal Content which includes transformation by conducting fundraising methods and collaborating synergies with national zakat institutions and zakat givers (muzakki); 3) strategic renewal Process which includes sustainability and unsustainability by conducting zakat management training and multi-line organizational networks, then the innovations made by Lazismu Yogyakarta, namely: 1) Relative advantage through the distribution of zakat that is right on target, the development of service programs, and cooperation related to digital distribution of zakat; 2) Compatibility, through increasing the capacity of Human Resources (HR) and poverty alleviation through 6 pillars namely education, economy, health, social da'wah, humanity and environment; 3) Complexity, through openness in the distribution of zakat through the Lazismu Yogyakarta website and targeted distribution; 4) Triability, through certainty in channeling zakat funds to recipients through fundraising methods; 5) Observability, by supervising the management and distribution of zakat and collecting data on muzakki and mustahik properly.